Grape Pomace Inhibits Colon Carcinogenesis by Suppressing Cell Proliferation and Inducing Epigenetic Modifications in an AOM/DSS Mouse Model - Tian, Qiyu (Curr Dev Nutr, 2020)
OBJECTIVES: Grape pomace (GP), a by-product of the wine and juice industry, is rich in bioflavonoids and dietary fibers. We hypothesized that grape pomace has protective effects against colitis-associated colorectal cancer (CRC). METHODS: Nine-week-old female mice were fed a control diet (CON) or CON with 5% grape pomace (GP) for 2 weeks, when mice were subjected to azoxymethane (AOM)/dextran sulfate sodium (DSS) for colorectal cancer (CRC) induction. All animals were received 1% DSS in drinking water for 7 days followed by a 21-day recovery in a 3-cycle experimental period, while receiving their respective diet. RESULTS: GP supplementation ameliorated the disease activity index (DAI) score, reduced tumor number, tumor size and pathological scores in AOM/DSS treated mice. Furthermore, dietary GP suppressed colonic expression of inflammatory cytokines, IL-1β and TNF-α, and inhibited NF-κB inflammatory signaling. Colorectal inflammation is known to enhance Wnt signaling and cell proliferation. In agreement, the content of β-catenin, a key downstream mediator of Wnt signaling, was reduced so for the expression of Cyclin D1 phosphorylation and content of p53 and PCNA level in GP-fed mice.  In addition, GP reduced the expression of ALDH1, a marker of cell stemness, and increased the expression of Cdx2, a key transcription factor initiating epithelial cell differentiation. Consistently, DNA methylation of the promoter region of Cdx2 gene and hypermethylation of GpG island methylator phenotype (CIMP), which commonly occurs during CRC carcinogenesis, was alleviated in GP group. CONCLUSIONS: GP supplementation suppressed colitis-associated CRC carcinogenesis associated with the suppression of inflammation and cell proliferation and the enhancement of DNA demethylation in Cdx2 and CIMP genes in the colon. FUNDING SOURCES: USDA-NIFA 2018–67,017-27,517.